APLIKASI UU NOMOR 6 TAHUN 2014 DALAM MEWUJUDKAN KESEJAHTERAAN MASYARAKAT PEDESAAN - Moh Rosyid (Program Studi Hukum Keluarga Islam, 2015)
The Law No 6/2014 on Village Government is the legal basis for the development of village community. There are six areas coordinated by the Ministry of Rural, Rural Development and Transmigration: village movement, village officials’ institutional capacity, establishment of five thousand BUMDes, revitalization of rural markets, rural infrastructure development, and online network connections in the village. A wise step to do all elements of the nation are participating and evaluating to realize the construction of a prosperous village.